EFL STUDENTS' PERCEPTION ON ENGLISH LEARNING MEDIA: WORD BANK - Rahmasagita, Deta Loliana; Degeng, Putu Dian Danayanti (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
Learning vocabulary is a crucial component of learning the English language. The four essential abilities in English for Second Language Learners will be easier to acquire through vocabulary mastery. Students' lower enthusiasm to learn a second language may have a background related to their lack of L2 vocabulary maintenance. Games are one the interactive media that can be applied in the classroom. This study was carried out to investigate how 13 students felt about the interactive game Word Bank when learning English in class. Senior High School Widyagama Malang grade 12 students served as the study's subjects. These details were gathered from teacher interviews and observations of English classes. With the aid of qualitative research techniques, the data was gathered. Students were given a survey in the form of a Google Form, which was used to collect the data. Data analysis revealed that students responded well to the questionnaire. According to the study's findings, using Word Banks in English learning is highly desirable and effective for use in the classroom. Boredom can be decreased by involving class XII Senior High School Widyagama Malang students. The findings of this study can help educators choose engaging learning tools with plenty of content.